2020
DOI: 10.1111/cns.13435
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia promotes microglial pyroptosis via inhibiting mitophagy in hypoxemic adult rats

Abstract: Acute respiratory distress syndrome (ARDS) is a common critical disease in intensive care units (ICUs). 1,2 Persistent hypoxemia is a typical symptom of ARDS. Ventilations are always needed to correct hypoxemia. 3,4 To avoid or reduce pulmonary morbidity, low tidal volume ventilation is often applied. 5,6 The ventilation strategy will certainly result in hypercapnia, which is called "permissive hypercapnia". 7,8 Our previous study found that hypercapnia could induce IL-1β overproduction in hypoxia-activated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Recently, activation of mitophagy has been demonstrated to be a vital protective mechanism of MSC-exos against different diseases [ 24 , 25 ]. Importantly, the inhibitory effect of mitophagy on pyroptosis has been demonstrated in several reports [ 23 , 29 , 30 ]. In accordance with these results, the present study showed that MSC-exos treatment significantly upregulated the levels of mitophagy-related proteins in OGD/R-exposed BV-2 cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, activation of mitophagy has been demonstrated to be a vital protective mechanism of MSC-exos against different diseases [ 24 , 25 ]. Importantly, the inhibitory effect of mitophagy on pyroptosis has been demonstrated in several reports [ 23 , 29 , 30 ]. In accordance with these results, the present study showed that MSC-exos treatment significantly upregulated the levels of mitophagy-related proteins in OGD/R-exposed BV-2 cells.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that inhibition of mitophagy contributes to microglial pyroptosis [ 23 , 29 , 30 ]. Thus, we wondered whether mitophagy is involved in the protective effect of MSC-exos against OGD/R-induced microglial pyroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DG21175D) was used to detect the level of ROS. 15 Based on the manufacturer's instruction, the brain tissue samples were homogenized and then added into the special plate coated with antibodies that could capture ROS. After one‐hour incubation at 37°C, substrate A and B were added successively.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, many studies in recent years have shown a complex link between mitophagy and pyroptosis. The current prevailing view is that there is a negative feedback regulation between mitophagy and pyroptosis (Yu et al, 2019 ; Davidson et al, 2020 ; Ding et al, 2020 ). Activation of caspase-1 caused by inflammasome would inhibit mitophagy and further enhance mitochondrial damage.…”
Section: Interactions Between Pyroptosis and Mitochondrial Apoptosismentioning
confidence: 99%